PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA LEAFLET UNTUK MENINGKATKAN PENGETAHUAN DAN PERILAKU DALAM UPAYA MENERAPKAN PROTOKOL KESEHATAN PADA PEDAGANG DI CAR FREE DAY TEMANGGUNG - Wulandari, Tri Suraning; Anisah, Retno Lusmiati; Fitriana, Nur Gilang; Purnamasari, Ika (Jurnal Ilmiah Kesehatan, 2020)
Purpose: The purpose of this study is to determine whether there is an effect of health educationusing leaflet media in increasing the knowledge and the behavior of traders in Temanggung ‘CarFree Day’ as an effort in implementing health protocols to prevent the transmission of Covid 19Methods: The research applied pre-experimental design with one group pre-test post-test design. The number of samples is 48 respondents taken through purposive sampling techniqueResults: The results of univariate analysis showed that the respondents' knowledge increasedafter being given health education using leaflet media by 50% for each of good and sufficientknowledge. On the other side, the respondents' behavior increased by 41.7% good, 35.3%adequate, and 23% lack. The difference in the score of the knowledge level before and afterbeing given health education intervention using leaflet media was Z = -1,957, p <0.05), while onthe behavior aspect was Z = -2,283, p <0 , 05). Conclusion: Thus, it can be concluded that there is an increase in the knowledge and thebehavior of traders in the Temanggung ‘Car Free Day’ in implementing health protocols toprevent the transmission of Covid 19